Adult-onset diffuse leukoencephalopathy with axonal spheroids and pigmented glia presenting with acute stroke-like symptoms: A rare clinical scenario - Purohit, Bela (Radiol Case Rep, 2020)
Adult-onset diffuse leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) is a rare progressive degenerative white matter disease caused by mutations in the colony-stimulating factor-1 receptor gene. Patients commonly present in the 4th or 5th decade with variable clinical presentations including behavioral changes, dementia, parkinsonism, and motor dysfunctions, eventually leading to death within a few years. Although the disease is typically hereditary, sporadic cases are known to occur. The classic MRI features of ALSP include T2 hyperintensities in the frontal and parietal white matter, scattered foci of restricted diffusion in the white matter, age-advanced cerebral involutional changes, thinning and signal changes in the corpus callosum, absence of infratentorial involvement and lack of enhancement. CT commonly shows tiny calcifications in the corpus callosum and deep white matter. We report a unique case of sporadic ALSP that initially presented as young stroke with acute onset of left-sided hemiparesis and no preceding history of cognitive decline. However, subsequent cognitive and behavioral changes lead to the consideration of an alternative diagnosis. Stroke-like symptoms is a very rare primary presentation of this disease entity. We have highlighted the classic MRI and CT features that helped to guide its diagnosis in our patient and prompted early corroborative genetic testing.